2011
DOI: 10.1002/pssc.201084030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low energy electron irradiation on optical properties of InGaN/GaN light emitting structures

Abstract: The effect of low energy e‐beam irradiation on the InGaN related cathodoluminescence in the MQW InGaN/GaN LED structures with different number of quantum wells has been studied. It is shown that the e‐beam exposure leads to an increase of emission intensity and to a formation of new blue‐shifted emission bands. It is shown that the changes in the optical properties are determined by the excess carrier injection. The changes observed were associated with the local changes of InGaN content due to In and/or Ga di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
(29 reference statements)
2
12
0
Order By: Relevance
“…This is indeed happening in many MCL experiments. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] For InGaN/GaN multiple quantum well (MQW) LED structures, the effects of low energy electron beam irradiation (LEEBI) on optical properties, as detected by MCL, were studied in Refs. 6, 10, and 13-17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is indeed happening in many MCL experiments. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] For InGaN/GaN multiple quantum well (MQW) LED structures, the effects of low energy electron beam irradiation (LEEBI) on optical properties, as detected by MCL, were studied in Refs. 6, 10, and 13-17.…”
Section: Introductionmentioning
confidence: 99%
“…14 and 15, what is happening is the emergence of a new blue shifted MCL band in addition to the initial MCL band. Therefore, a possibility of LEEBI stimulated point defect diffusion 7,8,[14][15][16] and/or strain relaxation 8 has been invoked. In support of such a) Electronic mail: ihlee@jbnu.ac.kr interpretation, one can point to the results presented in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that LEEBI leads to an essential increase in the cathodoluminescence (CL) intensity (by more than two orders of magnitude in some structures) and to a blue shift of MQW‐related emission band. The effect does not depend on a number of QWs and was observed even in a structure with only one QW . As shown, the QW‐related emission band did not steadily shift under LEEBI but instead a new emission band, whose peak was shifted to higher energies relative to the initial one, emerged.…”
Section: Introductionmentioning
confidence: 76%
“…The effect does not depend on a number of QWs and was observed even in a structure with only one QW . As shown, the QW‐related emission band did not steadily shift under LEEBI but instead a new emission band, whose peak was shifted to higher energies relative to the initial one, emerged. The intensity of this peak increased with the irradiation dose.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation